Tindak Tutur Perlokusi pada Daftar Putar “Pengembangan Diri” yang terdapat dalam Channel Youtube Zenius - Lestari, Salima Asha; Pratiwi, Eka Kartika; Pratiwi, Syifana (UPA Bahasa Universitas Tidar And HISKI Kedu, 2024)
The research entitled Perlocutionary Speech Acts in the “Pengembangan Diri” Playlist on the Zenius YouTube Channel aims to explain the phenomenon of perlocutionary speech acts that occur in 8 videos on the “Pengembangan Diri” playlist. The method used in this research is a qualitative descriptive method. The data source is 8 videos in the “Pengembangan Diri” playlist on the Zenius YouTube channel. Data collection in this research used the note-taking method, where the researcher watched the video and then recorded data in the form of phrases and sentences containing perlocutionary speech acts. To analyze the types and functions of speech, researchers used the pragmatic equivalent method. The analysis focuses on the type of speech and the effects it has on the speaker.